Chronic developmental hypoxia alters rat lung immune cell transcriptomes during allergic airway inflammation. Issue 3 (7th February 2023) - Chu, Michelle; Gao, Huanling; Esparza, Patricia; Pajulas, Abigail; Wang, Jocelyn; Kharwadkar, Rakshin; Gao, Hongyu; Kaplan, Mark H.; Tepper, Robert S.
Abstract: Populations that are born and raised at high altitude develop under conditions of chronic developmental hypoxia (CDH), which results in pulmonary adaptations of increased lung volume and diffusion capacity to increase gas exchange. It is not clear how CDH may alter allergic inflammation in the lung. In this study, we sought to characterize the impact of CDH on immune cell populations in the rat lung during a murine model of asthma. Rats were bred and raised in either hypoxic (15% oxygen, CDH) or normobaric room air (20% oxygen). At 3‐weeks of age, animals were sensitized to ovalbumin (OVA) or physiologic saline (phosphate‐buffered saline [PBS]) as a control, followed by three consecutive days of intra‐nasal OVA or PBS at 6‐weeks of age. We then assessed airway reactivity and allergic‐associated cytokine levels. This was followed by single‐cell transcriptomic profiling of lung cell populations. In scRNA‐seq analysis, we assessed differentially expressed genes, differentially enriched functional pathways, immune cell exhaustion/activation markers, and immune cell secretory products. Our results show that while OVA heightened airway reactivity, CDH suppressed airway reactivity in OVA‐challenged and control animals. Through scRNA‐seq analysis, we further demonstrate that CDH alters the transcriptional landscape in the lung and alters transcriptional programs in immune cells. These data define CDH‐dependent changes in the lung that impact airway reactivity. Abstract : Populations that are born and raised at high altitude develop under conditions of chronic developmental hypoxia (CDH), which results in pulmonary adaptations of increased lung volume and diffusion capacity to increase gas exchange. It is not clear how CDH may alter allergic inflammation in the lung. In this study, we defined the impact of CDH on airway hyperreactivity and immune cell populations in the rat lung during a model of asthma.